Saúde mental e atenção psicossocial em desastres: comportamentos profissionais do psicólogo intervindo na resposta - Ricardo, Henrique do Nascimento (2022)
Response is a stage of disaster management contemplated in the National Policy for Protection and Civil Defence (in Portuguese, PNPDC). It encompasses actions during and immediately after the event as means to provide aid and assist those affected, as well as return essential services. Mental Health and Psychosocial Attention (SMAPS) care to all individuals affected is recommended in the literature. However, in Brazil, we identified the need for training of public healthcare providers for such action. Some of the skills for the field were mapped and may be useful in training programmes. Although criticised, skills and content models are widespread for professional training in different areas. In Brazil, another possibility is the model of professional behaviour. A teaching technology that uses this concept is the Programming of Conditions for Behaviour Development (in Portuguese, PCDC). PCDC's concept of behaviour is defined as the relationship between what the organism does, the context in which they do it, and what follows its occurrence. In order to develop a teaching program, it is necessary to analyse and break down target behaviours for a task. Clarity, objectivity, precision and conciseness of teaching objectives have been adopted as criteria. False teaching goals are criticized. Based on the model of professional behaviours, the objective of this study is to characterize the general class of behaviours “acting directly in mental health and psychosocial care of those affected in disaster responses”. The classes that compose it were organized based on a model of general classes of professional behaviour for direct intervention in different fields of action, and in the four levels of action in Mental Health and Psychosocial Support available in the Pyramid of the Interagency Standing Committee (in Portuguese, IASC). As a source of information, a set of possible psychologists' skills for crisis intervention and prevention of Post-Traumatic Stress in disaster response was selected, which have been mapped in a previous study. As a result of a 10-step procedure, 72 classes of behaviours were discovered and organized into range levels. The six most comprehensive classes were: (1) Characterizing the need for intervention in relation to the behaviours of those affected by disasters in an SMAPS care context; (2) Designing interventions; (3) Implementing interventions; (4) Evaluating interventions; (5) Improving interventions; (6) Communicating findings. The current PCDC procedure allowed for greater clarity on psychologists’ possible goals while caring for those affected in acute distress, which can be adopted in future training. Here we placed greater emphasis on characterizing the class “Applying Psychological First Aid techniques”, but the procedure may be useful in discovering other classes of behaviours that make up SMAPS care in the response. This technology is also a possibility for discovering classes that make up the implementation in other phases of comprehensive risk and disaster management, as described in the PNPDC, such as prevention, mitigation, preparation, and recovery.